2014
DOI: 10.1645/13-300.1
|View full text |Cite
|
Sign up to set email alerts
|

Pro-Inflammatory Cytokines in the Serum of Silver Catfish (Rhamdia quelen) Naturally Infected byClinostomum complanatum: A Preliminary Study

Abstract: Clinostomum complanatum is a zoonotic parasite of birds, and its larval form (metacercariae) may cause disease in fish. The immune response of fish infected by C. complanatum is unknown, and therefore the objective of this study was to evaluate serum levels of pro-inflammatory cytokines in silver catfish (Rhamdia quelen) infected by this parasite. The analysis showed that fish infected with metacercariae presented significantly (P < 0.05) higher levels of tumor necrosis factor alpha (TNF-α), interleukin 1 (IL-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(3 citation statements)
references
References 8 publications
0
3
0
Order By: Relevance
“…Studies in several species of fish including rainbow trout, Oncorhynchus mykiss ; turbot, Psetta maxima ; goldfish, Carassius auratus ; and catfish, Bagre bagre , have shown that TNF‐α is an important macrophage activator considered to be a proxy indicator of innate immunological competence in both adults and larvae (Zou et al ; Lam et al ; De Lima et al ; Muñoz et al ). The assessment of TNF‐α concentration showed that larvae fed EE‐enriched nauplii had 929.3 ± 291.3 fg/mg, while the control larvae had 647.5 ± 303.4 fg/mg; however, the difference was nonsignificant because of the high dispersion of responses (Table ).…”
Section: Resultsmentioning
confidence: 99%
“…Studies in several species of fish including rainbow trout, Oncorhynchus mykiss ; turbot, Psetta maxima ; goldfish, Carassius auratus ; and catfish, Bagre bagre , have shown that TNF‐α is an important macrophage activator considered to be a proxy indicator of innate immunological competence in both adults and larvae (Zou et al ; Lam et al ; De Lima et al ; Muñoz et al ). The assessment of TNF‐α concentration showed that larvae fed EE‐enriched nauplii had 929.3 ± 291.3 fg/mg, while the control larvae had 647.5 ± 303.4 fg/mg; however, the difference was nonsignificant because of the high dispersion of responses (Table ).…”
Section: Resultsmentioning
confidence: 99%
“…In fish, inflammation is an important immune defense mechanism in response to tissue damage and infection [ 35 ]. Tissue damage and infection induce the activation and release of proinflammatory cytokines, such as IL-1β , IL-2 , IL-8, and TNF-α , which mediate the onset of innate immune response [ 36 , 37 ]. In this study, the mRNA expression levels of IL-1β , IL-2 , IL-8, and TNF-α were significantly upregulated in fish fed a diet containing 251.8 g/kg carbohydrate level.…”
Section: Discussionmentioning
confidence: 99%
“…The mean larval fluke size was, however, still lower, although the parasites were recovered from larger fish collected during late autumn, when the metacercariae were expected to be fully developed. A high proportion of underdeveloped parasites found in the additional sampling of round gobies implied that the development of B. polymorphus larvae in round gobies was limited by an immunological [ 48 ] or physiological [ 47 ] constraint rather than simply due to smaller host size.…”
Section: Discussionmentioning
confidence: 99%